2020
DOI: 10.21802/acm.2020.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Dental Orthopedic Morbidity Among Drafted Men Residing in Ivano-Frankivsk Region

Abstract: The objective of the research was to establish the level of dental orthopedic morbidity among draftees in the western region of Ukraine. Materials and Methods. A clinical dental examination of 294 drafted men residing in Ivano-Frankivsk region was carried out; among them, there were 185 urban residents and 109 rural residents. Results. There were established a quite high prevalence of dental orthopedic morbidity and intensity of its development, especially among rural residents - 275.7 and 522.9 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…and co-authors analysing oral hygiene among both conscripts and contract soldiers found out that the level of hygiene was "satisfactory" and "unsatisfactory", and only in some categories of servicemen 11.50% it was "good". This indicates on a lack of sanitary and educational work [12].…”
Section: Dentistrymentioning
confidence: 99%
“…and co-authors analysing oral hygiene among both conscripts and contract soldiers found out that the level of hygiene was "satisfactory" and "unsatisfactory", and only in some categories of servicemen 11.50% it was "good". This indicates on a lack of sanitary and educational work [12].…”
Section: Dentistrymentioning
confidence: 99%